The CDH Study Group: Past, Present, and Future - Holden, Kylie I.; Ebanks, Ashley H.; Lally, Kevin P.; Harting, Matthew T. (European Journal of Pediatric Surgery, 2024)
The Congenital Diaphragmatic Hernia Study Group (CDHSG) is an international consortium of medical centers actively collecting and voluntarily contributing data pertaining to live born congenital diaphragmatic hernia (CDH) patients born and/or managed at their institutions. These data are aggregated to construct a comprehensive registry that participating centers can access to address specific clinical inquiries and track patient outcomes. Since its establishment in 1995, 147 centers have taken part in this initiative, including 53 centers from 17 countries outside the United States, with 95 current active centers across the globe. The registry has amassed data on over 14,000 children, resulting in the creation of over 75 manuscripts based on registry data to date. International, multicenter consortia enable health care professionals managing uncommon, complex, and diverse diseases to formulate evidence-based hypotheses and draw meaningful and generalizable conclusions for clinical inquiries. This review will explore the formation and structure of the CDHSG and its registry, outlining their functions, center participation, and the evolution of data collection. Additionally, we will provide an overview of the evidence generated by the CDHSG, with a particular emphasis on contributions post-2014, and look ahead to the future directions the study group will take in addressing CDH.
Keywords: congenital diaphragmatic hernia; CDH Study Group; registry; prenatal diagnosis; diaphragmatic defect; extracorporeal membrane oxygenation; outcomes